Would Household Medical Expenditure Affect Chinese Citizens to Have More Children? - Chang, Jing; Wang, Meixin (Frontiers in Public Health, 2022)
This research investigates how household medical expenditure affects Chinese citizens having more children. We examined the causal relationship and found a negative influence of household medical expenditure on the willingness to have more children, confirming that increasing household expenditure on medical care may specifically decrease the high willingness. Chinese policymakers should adopt appropriate and effective strategies to mitigate the potential negative effects of household medical expenditure on the birthrate. These analyses emphasize the importance of promoting economic growth, increasing public health expenditure, and increasing medical security in the context of population imbalance and the trend of a rapidly aging society in order to encourage people to have more children, thereby slowing population decline.